Ex-combatants and the Truth Commission in Colombia: an analysis of the participation of former military and ex-guerrillas - Ugarriza, Juan Esteban (International journal of transitional justice, 2024)
The Colombian Truth Commission (2018 to 2022) provides a unique opportunity to delve into the participation of ex-military personnel and former guerrillas within truth-seeking bodies. While existing literature highlights the importance of their involvement in facilitating the assumption of responsibilities, rebuilding relations with their victims and undergoing personal transformation, it tends to overlook their potential contribution to truth and memory. After conducting interviews with former Commissioners, staff, soldiers and ex-guerrillas over a two-year period, our research reveals that former fighters maintained confrontational attitudes toward their previous adversaries. They primarily focused on promoting historical memory narratives rather than making substantial contributions to uncovering the truth. Conversely, the Commission took a moral stance in supporting the victims but failed to prevent conflicting narratives from hindering the path to reconciliation. The Colombian experience underscores the need for strategies to ensure that truth-seeking and memory spaces play a constructive role postconflict, and to accommodate perpetrators’ contributions to historical clarification without condoning their actions.